DEVELOPMENT OF A METHOD OF IMPROVEMENT OF QUALITY OF MILL PRODUCTS AND WEAR RESISTANCE OF THE TOOL AT THE ROLLING MILL 150 JSC «BSW – MANAGING COMPANY OF HOLDING «BMC» - I. A. Zuyeu (Литьë и металлургия)
Enhancement of calibration of mill rolls of the rolling mill 150, to improve of the mill products quality characteristics and to increase efficiency of the whole production is described in the article.